PENGARUH SERVICE DELIVERY SYSTEM TERHADAP LOYALITAS NASABAH PENABUNG - Rohmial . (Catholic University Musi Charitas, 2018)
The objectives of this study are : 1) the application of service delivery system that can be applied by Bank Rakyat Indonesia in Palembang, 2) the influence of physical support and contact personnel on customers, 3) the influence of service delivery system on customer loyalty at Bank Rakyat Indonesia in Palembang. This study is conducted by survey method so as to describe the participants response. The samples are taken by using simple random sampling with 100 respondents. The data collection instruments were observations, questionnaires, and interviews. The data collected was analysed by using descriptive and matrix analysis. The results of this research shows that all independent variables (physical support and contact personnel) significantly and positively influence the dependent variables (loyalty of the customers).